A Seropositive Nodular Rheumatoid Polyarthritis without Arthritis: Does It Exist? - Fatma Ben Fredj Ismail; Amel Rezgui; Monia Karmani; Olfa Ben Abdallah; Samira Azzebi; Chedia Laouani Kechrid (Case Reports in Medicine)
The rheumatoid polyarthritis is the most frequent chronic polyarthritis. It affects essentially the woman between 40 and 60 years. Rheumatic subcutaneous nodules and tenosynovitis are usually associated with seropositive symptomatic rheumatoid polyarthritis. It is, however, rare that they constitute the essential clinical expression of the disease. In this case, it makes dispute another exceptional form of rheumatoid arthritis such as rheumatoid nodulosis. A 60-year-old woman was hospitalized for tumefaction of the dorsal face of the right hand evolving two months before. The clinical examination found subcutaneous nodules from which the exploration ended in rheumatoid nodules with tenosynovitis. The evolution after four years was favourable under corticosteroid therapy, methotrexate, and colchicine.